An Efficient Power Control Technique for High-Frequency Resonant Inverter in Induction Heating System - Kumar, A.; Sarkar, D.; Sadhu, P. K. (Engineering, Technology & Applied Science Research, 2018)
An efficacious and reliable power control technique has been developed which can be used to regulate the output power of a high-frequency full bridge series resonant inverter (HF-FBSRI) in an induction heating (IH) system. In this paper, a modified buck-boost converter is presented to control the DC link/bus voltage which maintains the IH system under resonant mode and optimizes the performance of the IH system. Controlled DC link/bus voltage has been applied to this HF- FBSRI to control the average output power in the IH system. Using this aimed control technique, a wide range of output powers has been controlled and consistent performance of the IH system has been achieved. ZVS switching technique has been used to reduce the switching losses. Varying average power has been obtained at different duty cycles ranging from 0.2 to 0.8 with variable DC link voltage and it has been corroborated using PSIM environment for an IH system rated at 5500W.